A Compendium on International Trade in Lesotho - Denis N. Yuni; Tsotang Tsietsi; Motlamelle Kapa; Noah E. Attah; Sean Maliehe; Letzadzo Kometsi; Carol C. Ngang; Josphine Hapazari; Ojo J. Adelakun; Joalane Tota; Tšoamathe ‘Maseribane; Nthatisi Leseba; et al. (AOSIS, 2025)
International trade is a topic that is important for all states, regardless of their level of development. Trade can directly increase foreign exchange earnings and allow consumers to access desired foreign goods and services. Indirectly, trade potentially increases employment and improves technology (via spillover effects). It ultimately improves economic growth and enhances living standards. Conversely, there can be negative effects to trade, especially when imports are high. Examples are jobs being outsourced, increased economic dependence, de-industrialisation in importing countries, as well as exposure to negative external shocks. Therefore, it is crucial to critically examine the multifaceted ways that international trade manifests in any economy. It is on this premise that this compendium interrogates various aspects of international trade in the context of Lesotho. Although Lesotho is a small country, it is strategically located relative to South Africa, which gives it several trade advantages. The country is willing to engage in international trade and investment deals, and it is a member of several significant trade agreements that facilitate its integration into regional and global markets. Examples of these are the African Growth and Opportunity Act (AGOA), the Southern African Customs Union (SACU), the Southern African Development Community (SADC) Free Trade Area, and the Tripartite Free Trade Area, which combines the Common Market for Eastern and Southern Africa (COMESA), SADC and the East African Community. Understanding the various dimensions of international trade in Lesotho is imperative for investors, scholars and international business firms but published international trade literature on Lesotho is very scarce. This compendium brings to light the implications of international trade on the history and legal, political, social, geographical and economic realities of Lesotho. The book will also have a wide appeal for similar economies beyond the particular geographical context of Lesotho.